2012
DOI: 10.1111/j.1349-7006.2012.02360.x
|View full text |Cite
|
Sign up to set email alerts
|

Combination of ADH1B*2/ALDH2*2 polymorphisms alters acetaldehyde‐derived DNA damage in the blood of Japanese alcoholics

Abstract: The acetaldehyde associated with alcoholic beverages is an evident carcinogen for the esophagus. Genetic polymorphisms of the alcohol dehydrogenase 1B (ADH1B) and aldehyde dehydrogenase 2 (ALDH2) genes are associated with the risk of esophageal cancer. However, the exact mechanism via which these genetic polymorphisms affect esophageal carcinogenesis has not been elucidated. ADH1B*2 is involved in overproduction of acetaldehyde due to increased ethanol metabolism into acetaldehyde, and ALDH2*2 is involved in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
44
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 39 publications
4
44
0
Order By: Relevance
“…Figure 2B). These finding were consistent with the well-recognized dominant role of the ALDH2*2 genotype in affecting enzymatic activities [5][6][7]17,18 and indicated that the genotype existed mainly as the heterozygote ALDH2*1/*2 ( Figure 3A and 3B).We therefore combined heterozygote (ALDH2*1/*2) and homozygote (ALDH2*2/*2) as a single category of ALDH2*2 or ALDH2*2 carriers and compared them with the wild homozygote ALDH2*1*1 in the analyses. Figure 4A and 4B).…”
Section: Genotype Distribution Of Adh1b and Aldh2supporting
confidence: 90%
See 4 more Smart Citations
“…Figure 2B). These finding were consistent with the well-recognized dominant role of the ALDH2*2 genotype in affecting enzymatic activities [5][6][7]17,18 and indicated that the genotype existed mainly as the heterozygote ALDH2*1/*2 ( Figure 3A and 3B).We therefore combined heterozygote (ALDH2*1/*2) and homozygote (ALDH2*2/*2) as a single category of ALDH2*2 or ALDH2*2 carriers and compared them with the wild homozygote ALDH2*1*1 in the analyses. Figure 4A and 4B).…”
Section: Genotype Distribution Of Adh1b and Aldh2supporting
confidence: 90%
“…17,18 The carriers of ALDH2*2 thus manifest the characteristic of AFS caused by accumulation of ethanol-derived acetaldehyde. [5][6][7] We have shown that CSA is associated with AFS. 9 We and others also reported that CSA was induced by alcohol drinking, particularly in those with AFS.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations